Eighteen months of non-union of an upper third tibial fracture treated with Ayurvedic herbal medicines and Panchakarma: A case report - Sadanand P. Sardeshmukh; Sharad Hardikar; S. Prakash; Ranjit G. Nimbalkar; Anil T. Pawar; Akshay M. Baheti; Manasi R. Nimbalkar (Journal of Ayurveda and Integrative Medicine, 2025)
In the present case, a 29-year-old male met with a road traffic accident and sustained a closed comminuted fracture of the upper third (U/3) of the tibia of his left leg. The patient was operated (Open Reduction Internal Fixation, ORIF) with internal nailing. Even after 18 months, the fracture line was visible in the X-ray, so he was re-operated (ORIF) and the nail was replaced by plate fixation. However, after the second operation, the patient developed foot drop and hyperesthesia due to peroneal nerve injury. In view of this complicated history, the patient was suggested to take supportive Ayurvedic medicines and Panchakarma to hasten the healing process. The Ayurvedic medicines Lakshadi guggul 500 mg, Mashadi Yoga 500 mg and Asthi majja yoga 500 mg three times a day were started. The follow-up X-ray examination after eight months of treatment didn't show considerable callus at the fracture site, so Panchakarma therapy was given for 21 days. Callus formation was seen within 3 weeks after completing Panchakarma treatment. The oral medications were continued and a follow-up X-ray examination on two more months of treatment showed near complete healing (Fracture line was obliterated because of considerable callus). The medicine was continued for two more months. Afterwards, the patient came back after one year and the follow-up X-ray examination showed complete healing. The internal plate was removed and complete fracture recovery was reported. Thus, a patient with a non-union fracture of the tibia was treated successfully with add-on Ayurvedic medicines and Panchakarma therapy.